A Literature Study on Complementary Therapies for the Management of Anemia in Adolescent Girls - Tri Sartika; Ayu Devita Citra Dewi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Anemia is a common health issue among adolescent girls, primarily due to increased iron demands during growth and menstruation. This literature study aims to synthesize existing research on complementary therapies for managing anemia in this population. The study employed a literature review design with a systematic search of scientific articles published between 2018 and 2025. Data were collected from multiple electronic databases, including PubMed and Google Scholar, using keywords such as